Analysis of Qris Application as a Patented Computer Program Based on Patent Law - Jessicha (Asosiasi Dosen Muda Indonesia, 2026)
Discusses the analysis of the Quick Response Code Indonesian Standard (QRIS) application as a computer program from the perspective of Law Number 13 of 2016 concerning Patents. This study aims to examine whether QRIS can be qualified as an object of patent protection or is included in the category excluded by patent law in Indonesia. The research method used is a normative juridical approach by examining the provisions of laws and regulations, legal doctrine, and the concept of intellectual property protection for computer programs. The results of the analysis show that QRIS is essentially a digital payment system and standard that emphasizes methods, protocols, and interoperability between payment service providers, so it does not meet the qualifications as a patentable technical invention. The computer program that is part of QRIS is more appropriate to obtain legal protection through the copyright regime or other protection mechanisms outside of patents. The conclusion of this study confirms that although QRIS has innovation value and significant contributions to the national payment system, patent protection for QRIS still has legal limitations based on the provisions of patent law in force in Indonesia.